Design and development of vacuum fruit frying machine for SMI and SME application - Ahmad Bakri, Abdul Aziz (2009)
Frying in vacuum condition is a new technology that can be used to improve the quality of fried foods such as chips and fruit vacuum frying machines suitable because it is working in low temperatures and use the minimum oxygen content. The most significant difference between frying exposed to atmospheric and vacuum conditions are frying in humidity and sliced fruit color after frying. Shown promise for vacuum frying techniques that can be used to reduce the oil content in fried sliced fruit while maintaining color and taste products. especially. In the vacuum frying process, the process of drying the fruit slices before frying will occur and it will give better results than frying exposed to the atmosphere. For example fried sliced fruit that will be absorbed vacuum drying and this will reduce the moisture in the fruit slices and this will reduce frying time.